2019
DOI: 10.1098/rsos.182060
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of surface-modified hydroxyapatite into poly(methyl methacrylate) to improve biological activity and bone ingrowth

Abstract: Poly(methyl methacrylate) (PMMA) is the most frequently used bone void filler in orthopedic surgery. However, the interface between the PMMA-based cement and adjacent bone tissue is typically weak as PMMA bone cement is inherently bioinert and not ideal for bone ingrowth. The present study aims to improve the affinity between the polymer and ceramic interphases. By surface modifying nano-sized hydroxyapatite (nHAP) with ethylene glycol and poly(ɛ-caprolactone) (PCL) sequentially via a two-step ring opening rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…According to that standard, the oHAP-BC group included only one sample (oHAP5-BC that contained a low loading of oHAP, at 5 wt.%) that met the requirements, while all six samples of the vHAP-BC and gHAP-BC groups met the ISO 5833 requirements for bending and compressive properties, indicating the effectiveness of organic functional HAPs when applied in bone cements. Although there is no requirement for TS, TM and CM in the ISO 5833 standard, the obtained results for the tensile properties and compressive modulus in this study are in the tolerance range observed for commercial bone cements in other works [25,40,[54][55][56][57].…”
Section: Mechanical Propertiessupporting
confidence: 49%
“…According to that standard, the oHAP-BC group included only one sample (oHAP5-BC that contained a low loading of oHAP, at 5 wt.%) that met the requirements, while all six samples of the vHAP-BC and gHAP-BC groups met the ISO 5833 requirements for bending and compressive properties, indicating the effectiveness of organic functional HAPs when applied in bone cements. Although there is no requirement for TS, TM and CM in the ISO 5833 standard, the obtained results for the tensile properties and compressive modulus in this study are in the tolerance range observed for commercial bone cements in other works [25,40,[54][55][56][57].…”
Section: Mechanical Propertiessupporting
confidence: 49%
“…PMMA/BAG composites have shown good bioactivity as well as enhanced mechanical strength [148,161,162]. For instance, composite of PMMA and silicate-based bioceramic showed good cell attachment, proper setting time and high mechanical strength as compared to PMMA alone [161].…”
Section: Polymeric Matrix Composite Materialsmentioning
confidence: 99%
“…Ku et al prepared PMMA composite with surface-modified HA, in order to enhance ceramic-polymer phase interaction. HA nanoparticles were modified with either ethylene glycol or ɛ-caprolactone before blending with PMMA; this enhanced the compressive strength of the composite along with improved bioactive surface [162]. Furthermore, PMMA/BAG custom-made craniofacial implants were clinically applied to repair calvarial and facial defects; 5-year follow-up found patients' clinical recovery with good aesthetic and functional outcome [113].…”
Section: Polymeric Matrix Composite Materialsmentioning
confidence: 99%
“…With the development of biomaterial medicine, artificial bone scaffolds served as an alternative solution have shown promising potential to treat periodontal tissue bone defect. Many natural and synthetic materials such as collagen, glass ceramics, calcium sulfate, natural and artificial polymers are considered cell carriers and bone conduction materials [ 8 ]. Like the mineral phase of bone tissue, β-tricalcium phosphate (β-TCP) has appropriate biocompatibility, bioactivity, and osteoconductive ability.…”
Section: Introductionmentioning
confidence: 99%